Financial results on twenty-five farms in mid-Roscommon in 1948-1949 - O'Connor, R. (Statistical and Social Inquiry Society of Ireland, 1950)
It should be explained at the outset that the main object of these inquiries is not so much to examine financial conditions in this district as to show ways and means of carrying out a more broadly based survey. In other words, these are pilot surveys conducted for the purpose of determining the type of question that should be asked to obtain reasonably accurate replies.
Read before the Society, 10 February 1950
Keywords: Farm level financial results; Roscommon -- Farming; Farm level analysis of Irish agriculture; Farming -- Roscommon; Farms -- Roscommon; 314.15